Use of alternative fuels in compression ignition engines: a review. Issue 4 (4th July 2019) - Kumar, Shiva; Dinesha, P.
ABSTRACT: This paper reviews the results of various researchers from different countries who prepared biofuels from vegetable oils and animal fats. The performance and emission characteristics can be improved by blending with petrodiesel, changing the fuel injection parameters, adding oxygen-rich fuel additives and employing intake air oxygen enrichment methods. NOx emissions can be minimised by using exhaust gas recirculation techniques. From this review, it can be concluded that the use of biofuels as an alternative fuel for compression ignition engines improves the performance and emissions by adopting suitable combustion improvement methods.